2016
DOI: 10.3233/sji-161009
|View full text |Cite
|
Sign up to set email alerts
|

Imputation research for the 2020 Census1

Abstract: Abstract. For the 2010 Census, the count imputation procedure filled in housing unit status and size for the small proportion of addresses (less than one-half percent) where this information was unknown. The small proportion was due in part to an extensive nonresponse followup (NRFU) field operation geared towards resolving addresses so that a status and count were known. For 2020, the Census Bureau is researching two changes to the NRFU field operation to reduce cost. The first is the possible use of administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…. SeeKeller (2016) for a comparison of direct use of AR and traditional imputation modeling for the cases that are unresolved at the conclusion of the NRFU operation.…”
mentioning
confidence: 99%
“…. SeeKeller (2016) for a comparison of direct use of AR and traditional imputation modeling for the cases that are unresolved at the conclusion of the NRFU operation.…”
mentioning
confidence: 99%
“…However, the approach can be implemented adaptively as new administrative record information is obtained during the NRFU operation. In the context of the 2015 Census Test, Keller (2016) describes multi-phased integration of administrative record modeling as an adaptive component throughout NRFU. For this test, after initial AR Occupied and AR Vacant cases were identified, the Census Bureau received additional IRS 1040 and IRS 1099 information.…”
Section: Adaptive Uses Of the Distance Function Methodsmentioning
confidence: 99%
“…The distance function methodology can also be used after data collection is complete, as an alternative to unit imputation of status and population size for unresolved housing units. In the context of the 2015 Census Test, Keller (2016) documents a modification of the optimization approach: refitting and determining AR Vacant and AR Occupied cases by lowering the average constraint values in the optimization approach -thus identifying more AR Vacant and AR Occupied cases. The new cases that remained unresolved addresses after the full visit strategy are assigned occupancy status and enumerated using administrative records rather that via an imputation.…”
Section: Adaptive Uses Of the Distance Function Methodsmentioning
confidence: 99%
“…Unfortunately, though, there are serious issues regarding the completeness and accuracy of administrative records. For example, the Census Bureau found that about 20% of housing units determined to be vacant using administrative records in census tests conducted in 2016 in Los Angeles County, California, and Harris County, Texas, were actually occupied 3 …”
Section: Non‐response Follow‐upmentioning
confidence: 99%